Upaya Penurunan Intensitas Halusinasi Dengan Memotivasi Melakukan Aktivitas Secara Terjadwal - Annis, Muhamad; , Arif Widodo, A.Kep., M.Kes (2017)
The background : The estimated that clients with skizofren 90% having aural hallucinations.Hallucinations are form of the symptoms of positives that happens very often at the patient's disorder that.Clients with sensory hallucinations are not capable or wrong in with stimulating the senses although the actual stimulus it does not exist,if the client having these hallucinations or an illusion.If interpretation of stimulating the senses that are not in accordance with the stimulus that accepted.There are many kinds of hallucinations and most of the auditory hallucinations,our clients with auditory hallucinations can be control with motivation to patients about the importance of making the activity was scheduled. Objectives: The writer can understand can practice the nursing in patients with a diagnosis of the perceptions of sensory. Methods: The method used is descriptive,sources used by writer in get from interviewing,thelibrary,study the documents and observe.In interviews and observations be done directly on patients from the assessment,intervention,implementation and evaluation. Results: After did the nursing three days,patients with impaired perception of sensory,auditory hallucinations can get to know her hallucinations are experienced and can control and than reduce the intensity of auditory hallucinations with how to do activities that had been scheduled. Conclusion : The nursing is resolved in a part,to require further treatment and cooperation with the medical team,clients ,and family indispensable to the success of the nursing,There the reduction in the intersity of hallucinations before and after given intervention.